Increased reaction times and reduced response preparation already starts at middle age - Wolkorte, Ria; Kamphuis, Janine; Zijdewind, Inge (Frontiers in Aging Neuroscience, 2014)
Generalized slowing characterizes aging and there is some evidence to suggest that this slowing already starts at midlife. This study aims to assess reaction time changes while performing a concurrent low-force and high-force motor task in young and middle-aged subjects. The high-force motor task is designed to induce muscle fatigue and thereby progressively increase the attentional demands. Twenty-five young (20-30 years, 12 males) and sixteen middle-aged (35-55 years, 9 males) adults performed an auditory two-choice reaction time task (CRT) with and without a concurrent low- or high-force motor task. The CRT required subjects to respond to two different stimuli that occurred with a probability of 70% or 30%. The motor task consisted of index finger abduction, at either 10% (10%-dual-task) or 30% (30%-dual-task) of maximal voluntary force. Cognitive task performance was measured as percentage of correct responses and reaction times. Middle-aged subjects responded slower on the frequent but more accurately on the infrequent stimuli of CRT than young subjects. Both young and middle-aged subjects showed increased errors and reaction times while performing under dual-task conditions and both outcome measures increased further under fatiguing conditions. Only under 30%-dual-task demands, an age-effect on dual-task performance was present. Both single- and dual-task conditions showed that already at mid-life response preparation is seriously declined and that subjects implement different strategies to perform a CRT task.